No - Rueda, Claudia (Groundwood Books/House of Anansi Press, 2010)
It's winter and little bear doesn't want to go to sleep. He'd rather play, and he's sure he won't get cold outside, no matter how long the winter is, how deep the snow might get, or how hard the storm might blow. Until, that is, little bear finds himself all alone in a snowstorm.